Метод расчета бифуркационных линий механических систем - Аврамов, К. В. (НТУ "ХПИ", 2004)
The method for bifurcation curves of forced oscillations of mechanical system is suggested in this paper. The example of transmission calculations is given.
Keywords: прикладная математика; бифуркации; срывы колебаний; матрица Якоби; нелинейные колебания; участок силовой передачи